Logging for the ark: improving the conservation value of production forests in South East Asia - Gustafsson, L.; Nasi, Robert; Dennis, R.A.; Nguyen Hoang Nghia; Sheil, Douglas; Meijaard, E.; Dykstra, D.P.; Priyadi, H.; Pham Quang Thu (Center for International Forestry Research, 2007)
In order to maintain the high levels of biodiversity and the ecological functions of tropical forest landscapes in South East Asia, production forests need to be managed in a more sustainable way. Numerous initiatives already exist in the form of codes of practice, criteria and indicators, and certification schemes in the countries of South East Asia, but to date such guidelines and standards have been vague and have lacked quantitative targets. Reducedimpact logging (RIL) is a concept related to techniques and practices that aim to achieve environmentally sound timber harvesting; the concept has gained broad acceptance in the tropics. As yet, however, RIL guidelines have focused mainly on environmental aspects such as soil and water, and have taken the flora and fauna into account to a minor degree only. In this report, detailed recommendations are made to help forest managers take account of biodiversity conservation in dipterocarp logged-over and primary natural forests where mechanised logging is practised. The recommendations are based on those made in the CIFOR publication Life after Logging, further developed through three workshops held under a joint project between the Swedish University of Agricultural Sciences, CIFOR and the Forest Science Institute of Vietnam. The recommendations are linked to the different phases of the forestry cycle: i.e. planning (inventories of sensitive species and habitats, delimitation of set-aside areas and riparian buffers), infrastructure (logging camps, roads, bridges, skid-trails, landings), logging (retention of critical structures, micro-habitats, key resources, felling techniques, harvesting intensity, site-adaption), post-logging (understorey slashing, rehabilitation of log-landings and stream crossings, re-forestation), and monitoring (biodiversity inventories). Issues related to hunting, fire, invasive species, domestic animals, traffic, and logging and conservation for local people are also covered.